Evaluasi Sistem Drainase Perkotaan Berdasarkan Curah Hujan Empat Tahun Terakhir : Studi Kasus Jalan Rumah Sakit Haji – Willem Iskandar - Raihan, Abiyan; Yoland, Yuni; Pratama, Al Fitra (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
Urban drainage systems play a critical role in conveying rainfall and preventing flooding in urban areas. However, changes in land use and inadequate maintenance can reduce the flow capacity of drainage channels, increasing the risk of waterlogging. This study aims to evaluate the performance of the urban drainage system based on four years of rainfall data (2020–2023) at Jalan Rumah Sakit Haji, Percut Sei Tuan District, Deli Serdang Regency, Medan City, Indonesia. A quantitative approach was applied using hydrological and hydraulic analysis. Primary data included field measurements of drainage channel dimensions and observations of physical conditions, while secondary data included daily rainfall records and drainage network maps. The design discharge was calculated using the Rational Method, and the existing channel capacity was determined using Manning's equation. The results show that 40% of the sampled channels can still accommodate the design discharge, while 60% experience reduced capacity due to sedimentation, debris blockage, and poor physical condition. High sediment accumulation, debris, and moss growth are the main factors reducing capacity, and the presence of animals such as monitor lizards indicates poorly maintained open channels. Technical recommendations include channel normalization, routine cleaning, local dimension improvements, sustainable drainage implementation, and regular monitoring and maintenance. This study provides scientific evidence to guide the improvement of urban drainage systems to reduce the risk of flooding.